2020
DOI: 10.1186/s13024-020-00362-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell-free mitochondrial DNA levels in Parkinson’s disease are influenced by treatment

Abstract: Several studies have linked circulating cell-free mitochondrial DNA (ccf-mtDNA) to human disease. In particular, reduced ccf-mtDNA levels in the cerebrospinal fluid (CSF) of both Alzheimer's and Parkinson's disease (PD) patients have raised the hypothesis that ccf-mtDNA could be used as a biomarker for neurodegenerative disease onset and progression. However, how a reduction of CSF ccf-mtDNA levels relates to neurodegeneration remains unclear. Many factors are likely to influence ccf-mtDNA levels, such as conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 52 publications
3
38
0
Order By: Relevance
“…In PD, the reduced vCSF-cfmtDNA we observed suggests that reduced cfmtDNA persists throughout the disease course with post-mortem vCSF-cfmtDNA levels comparable to those we observed in early-stage PD lumbar CSF 25,37 . How this relates to the neurodegenerative process in PD remains still unclear as we found no correlation between vCSF-cfmtDNA and neurodegenerative protein markers.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In PD, the reduced vCSF-cfmtDNA we observed suggests that reduced cfmtDNA persists throughout the disease course with post-mortem vCSF-cfmtDNA levels comparable to those we observed in early-stage PD lumbar CSF 25,37 . How this relates to the neurodegenerative process in PD remains still unclear as we found no correlation between vCSF-cfmtDNA and neurodegenerative protein markers.…”
Section: Discussionsupporting
confidence: 84%
“…Since then, cfDNA levels have been linked to a diverse range of phenotypes including sepsis 8 , myocardial infarction 9 and autoimmune disease 10 . More recently, research has demonstrated an association between cell-free-mitochondrial DNA (cfmtDNA) and several complex traits 11 23 , particularly neurological and neurodegenerative diseases such as PD 24 , 25 , AD 26 , 27 and multiple sclerosis (MS) 14 , 28 . Its stability in extracellular fluids such as plasma, serum and cerebrospinal fluid has led many studies to suggest that cfmtDNA has utility as a biomarker of disease onset and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced cf-mtDNA levels in the cerebrospinal fluid of neurodegenerative disease patients—including Alzheimer’s and Parkinson’s disease as well as multiple sclerosis—have also been reported. However, although reduced cf-mtDNA might be a hallmark of neurodegeneration, the utility of cf-mtDNA as a biomarker of such diseases is limited [ 52 , 53 ].…”
Section: Cell-free Dnamentioning
confidence: 99%
“…In animals, self-DNA of nuclear or mitochondrial origin is frequently reported to act as a DAMP and to determine various types of diseases. For instance, extracellular self-DNA is associated to several diseases and/or to their severity, like in cancers (Hawes et al, 2015), hypertension (McCarthy et al, 2015, and Parkinson and Alzheimer diseases (Lowes et al, 2020). Self-DNA is also considered to be involved in autoimmune diseases such as in rheumatoid arthritis (Rykova et al, 2017), in systemic lupus erythematosus (Barrat et al, 2005), and in other autoimmune diseases (Vakrakou et al, 2018).…”
Section: Exdna As a Dampmentioning
confidence: 99%